Pengaruh Faktor Geografi Terhadap Karakteristik Bambu Petung - Laksono, Andromeda Dwi; Agustiningtyas, Diah Tri (SPECTA Journal of Technology, 2019)
In this study was about a comparison of geographic factors towards the characterization of petung bamboo in Indonesia and the Philippines. Bamboo is one of the plants that has advantages in the field of technical materials based on developments in composite materials and is found in various regions. In general, bamboo has lignin and cellulose, where the morphology and nature of both bamboos are not the same from different countries. Therefore,material testing was carried out on each Indonesian and Filipino petung bamboo using material characterization testing methods. The process of Differential Scanning Calorimetry (DSC) was carried out to measure calorimetry with the yield of melting point in Philippine petung bamboo at 341ºC which is lower than the melting point in Indonesian petung bamboo which is 354.34ºC. In this DSC test, quantitative and qualitative results were obtainedin the form of phase changes, melting, and transition temperatures that occurred. Then an Energy Dispersive Spectrometer (EDS) was analyzed and the carbon content of cellulose and lignin was higher in Indonesian petung bamboo, respectively 65.29 wt.% And 66.05 wt.%. The morphology of bamboo shows that the fibers and matrices present in Philippine petung bamboo are denser than those of Indonesian petung bamboo. The highest peak value based on X-Ray Diffraction (XRD) is found in Philippine petung bamboo at 2? of 34.49 and cubic phase.